Effects of Hip Geometry on Fracture Patterns of Proximal Femur - Kazemi, Seyyed Morteza (Arch Bone Jt Surg, 2016)
BACKGROUND: Some studies have previously shown that geometry of proximal femur can affect the probability of fracture and type of fracture. It happens since the geometry of the proximal femur determines how a force is applied to its different parts. In this study, we have compared proximal femur’s geometric characteristics in femoral neck (FNF), intertrochanteric (ITF) and Subtrochanteric (STF) fractures. METHODS: In this study, 60 patients who had hip fractures were studied as case studies. They were divided into FNF, ITF and STF groups based on their fracture types (20 patients in each group). Patients were studied with x-ray radiography and CT scans. Radiological parameters including femoral neck length from lateral cortex to center of femoral head (FNL), diameter of femoral head (FHD), diameter of femoral neck (FND), femoral head neck offset (FHNO), neck-shaft angle (alpha), femoral neck anteversion (beta) were measured and compared in all three groups. RESULTS: Amount of FNL was significantly higher in STF group compared to FNF (0.011) while ITF and STF as well as FNT and ITF did not show a significant different. Also, FND in FNF group was significantly lower than the other two groups, i.e. ITF and STF. In other cases there were no instances of significant statistical difference. CONCLUSION: Hip geometry can be used to identify individuals who are at the risk of fracture with special pattern. Also, it is important to have more studies in different populations and more in men.